Challenges and barriers to healthy eating behaviors in the workplace: A pragmatic approach to promoting healthy aging - Mahnaz Khalafehnilsaz; Ali Ramezankhani; Rozina Rahnama (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The role of health-related behaviors, particularly eating behavior, in the health of middle-aged individuals in the workplace is crucial. This qualitative study aimed to gain a deeper understanding of the challenges and barriers to healthy eating behaviors in the industrial workplace from the perspectives of middle-aged workers and employers. METHODS: Semi-structured interviews were conducted with 15 participants, including 5 workers aged 35 to 59 years, 3 nutrition experts, 2 health, safety and environment (HSE) experts, and 5 employers from industrial workplaces in Tehran, Iran. Purposeful sampling was used to select participants who could provide meaningful insights into the research question. The data were analyzed using Graneheim and Lundman approach with MAXQDA software. RESULTS: The study revealed three main themes that hindered healthy eating behaviors in the workplace: (i) the absence of organizational structures for well-being and health, including sub-themes such as the lack of health-oriented organizational policies, inaccessibility to healthy nutritional resources, and restrictive rules, (ii) the pressure of organizational social norms, including sub-themes such as the impact of friendship networks and colleagues, and the effect of workplace culture, and (iii) the lack of a supportive learning environment for healthy behavior, including sub-themes such as the impact of poor interactions and the absence of supportive training. CONCLUSION: The findings highlight the need for workplace health programs that address the identified challenges and promote healthy eating behaviors among middle-aged workers. Implementing health-focused policies and fostering a workplace environment that encourages nutritious food choices can enhance the overall health and well-being of workers and potentially lead to healthy aging in the future.